PENINGKATAN PRESTASI BELAJAR BAHASA INDONESIA TENTANG KEMAMPUAN MEMBACA MENGGUNAKAN METODE MAKE A MATCH SISWA KELAS IV MI MA’ARIF SANGON KULON PROGO TAHUN PELAJARAN 2021/2022 - Djarijah Djarijah (Pedir Research Institut, 2022)
Abstract:. This study aims to describe efforts to improve Indonesian language learning achievement about reading skills using the make a match method in class IV at MI Ma'arif Sangon Kulon Progo. This research was conducted in class I MI Ma'arif Losari Salam, Salam District, Kab. Magelang Academic Year 2021/2022, with a total of 13 students, consisting of 8 male students and 5 female students. The time of the study was carried out from November to December in the odd semester of the 2021/2022 academic year. The subject that will be studied is Indonesian language reading ability. In collecting data, the researcher used test, observation, and documentation techniques. While the instruments used are in the form of observation sheets and learning outcomes test questions to determine whether there is an increase in student learning outcomes after learning using the Make a Match type cooperative learning model. The results showed that student learning outcomes increased after the action was taken. The percentage of students who have not completed has decreased from cycle 1 to cycle 2 (from 63.1% to 0%. The percentage of students who have completed has increased from cycle 1 to cycle 2 (from 37% to 100%). The indicators of the success of this study are , that this research is said to be successful if the percentage of students whose learning outcomes have been completed reaches a minimum of 85%.From the table shows that the percentage of students whose grades have completed has reached 100%, then this research has been successful.